Bile Acids in Gastroenterology Basic and Clinical - Tazuma, Susumu; Takikawa, Hajime; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
This book examines the biological aspects of bile acid analysis and their clinical applications, providing readers with an overview of cutting-edge discussions on Bile Acid research and diseases. It begins with detailed discussions on the biological aspects of bile acid, with chapters examining bile acid from various perspectives, from its metabolism to its use in therapeutic agents. Subsequent chapters focus on diseases involving bile acid abnormalities, and specific applications are addressed concerning gallstones, cholestatic liver disease, NAFLD/NASH, hepatitis, pancreatitis, esophageal cancer and colon cancer. In keeping with the book$1 (Bs integrated approach, the Editor has gathered a broad range of eminent scholars and practitioners to provide a comprehensive review of modern bile acid research. The book offers clinical physicians, basic researchers and postgraduate students essential insights into cutting-edge research and paves the way for further research.s
Part I Biological Aspects of Bile Acids -- Chapter 1 Metabolism of Bile Acids -- Chapter 2 Hepatobiliary Transport of Bile Acids -- Chapter 3 Intestinal Digestion and Absorption -- Chapter 4 Nuclear Receptor Regulation -- Chapter 5 Bile Acid as Therapeutic Agents -- Part II Bile Acids and Diseases -- Chapter 6 Bile Acids and Gallstones: Epidemiology, Pathogenesis, Diagnosis and Management -- Chapter 7 Bile Acids and Cholestatic Liver Disease 1: Primary biliary cholangitis (PBC) -- Chapter 8 Bile Acids and Cholestatic Liver Disease 2: Primary Sclerosing Cholangitis -- Chapter 9 Bile Acids and Cholestatic Liver Disease 3: Inborn Errors of Bile Acid Synthesis -- Chapter 10 Bile Acids and NAFLD/NASH -- Chapter 11 Bile Acids and Viral Hepatitis and Hepatocellular Carcinoma -- Chapter 12 Bile Acids and Pancreatic Disease -- Chapter 13 Bile Acids and Esophageal Cancer -- Chapter 14 Bile Acid and Colorectal Cancer -- Chapter 15 Bile Acids and Metabolic Syndrome.
Keywords: Medicine; Gastroenterology; Hepatology; Metabolic diseases; Medicine & Public Health; Gastroenterology; Metabolic diseases; Hepatology